Effective Disengagement: Insecure People Are More Likely to Disengage From an Ongoing Task and Take Effective Action When Facing Danger. Issue 2 (29th March 2017) - Ein‐Dor, Tsachi; Perry‐Paldi, Adi; Merrin, Jenna; Efrati, Yaniv; Hirschberger, Gilad
Abstract: Objective: People believe that they can respond effectively to threats, but actually they experience difficulties in disengaging from ongoing tasks and shifting their attention to life‐threatening events. We contend that this tendency is especially true for secure people with respect to their worldview and perception of others and not for insecure individuals. Method: In Study 1 ( N  = 290), we examined individuals' reactions to various threat scenarios. In Study 2 ( N  = 65), we examined these reactions using a behavioral design high in ecological validity. In Study 3 ( N  = 78), we examined group‐level benefits for the actions of insecure individuals by manipulating asocial behavior in response to an emergency. Results: Study 1 indicated that anxiously attached individuals stayed away from threats and sought help; avoidant people tended to take action by either assessing the risk of the event and/or enacting an asocial action such as fight or flight. Study 2 added ecological validity to these findings, and Study 3 showed that priming asocial behavior responses promoted actions that increased group members' chances of survival. Conclusion: Results validate the central tenets of social defense theory and indicate that actions that are deemed asocial may paradoxically promote the survival of individuals and groups.